Methodology for Defining the Digital Economy - Yu. V. Belousov; O. I. Timofeeva (Мир новой экономики)
The digital economy is a new, quite fast developing, social and economic phenomenon. The economic theory lags significantly behind the dynamics of this phenomenon. Until now, the term digital economy has been understood by analytical and empirical specialists as various phenomena and processes. In this article, we propose a new approach to defining the essence of the digital economy. Thus, we analyse available definitions of the term digital economy based mainly on the sectoral approach. Here arise problematic issues when using this approach to the definition of the digital economy. Besides, we make a distinction between the terms the digital economy and the digital sector of economy, as well as a criterion to distinguish the digital and non-digital economy. We pay much attention to new approaches to defining the digital economy. Some researchers based the research and the definition, taking into account the impact of a man as an operator of production processes acting on objects and instruments. On the contrary, in this article we define the digital economy as an economic activity of people focusing on a feature that the impact of a person as a manufacturer of products is not on objects of labour and instruments but management systems of such instruments. So, the non-digital economy is characterised by the impact of a person on objects or instruments. Firstly, the digital sector of the economy is production where a person influences the systems of instrument management. Secondly, the development and design of new systems of instrument management. Results of theoretical studies of the essence of the digital economy have essential applications. First of all, it concerns the issues of state policy development in the digital economy.